Reform of the international institutions : the IMF, World Bank and the WTO - Coffey, Peter; Riley, Robert J. (Cheltenham, UK ; Northampton, MA : Edward Elgar, 2006)
"At no period since the creation of the International Monetary Fund (IMF), World Bank and World Trade Organisation (WTO) has it been a more opportune time to examine the work, reform and future of the international monetary and trading systems. In this comprehensive examination, the authors provide original, independent assessments of these institutions from both an American and European perspective and offer proposals for reform and improvement."--Jacket
Includes bibliographical references (p. 156-162) and index.
rpm 24/08/16
Loans
Keywords: International finance; International Monetary Fund; World Bank; World Trade Organisation